Patterns of febrile seizures: analysing seasonal, diurnal and socioeconomic correlations in Bangladesh - Rahman, M. Ziaur; Salim, A. F. M.; Ghosh, Nabo Krishna; Sultana, Azmeri (International Journal of Contemporary Pediatrics, 2025)
Background: Febrile seizures (FS) are a common neurological disorder in children, often triggered by fever without evidence of central nervous system infections. This study explores the demographic, seasonal, diurnal and socioeconomic patterns of febrile seizures among children in Bangladesh. Methods: A cross-sectional study was conducted on 298 children aged 5 months to 5 years admitted with febrile seizures at a tertiary care hospital. Data were collected on demographic characteristics, comorbidities, seizure patterns and socioeconomic status and analyzed using descriptive statistics. Results: The majority of febrile seizures occurred in children aged 13–18 months (35.57%) with a male predominance (72.48%). Seizures were brief, with 50.34% lasting≤1 minute and most occurred within 6 hours of fever onset (51.01%). Diurnal variation showed the highest incidence between noon and evening (51.68%). A bimodal seasonal distribution was observed, with peaks in January (12.08%) and July (11.07%). Bronchiolitis (37.92%) and diarrhea (27.18%) were the most common comorbidities. Firstborn children (86.58%) and those with normal nutritional status (93.29%) were predominantly affected. Conclusions: Febrile seizures in the study population showed distinct demographic, temporal and socioeconomic patterns, aligning with global trends. The findings underscore the importance of early fever management, targeted interventions during seasonal peaks and caregiver education to reduce seizure-related morbidity.